Believability on the axes of structuralism: Yan Martel‘s Life of Pi - Habibi, Seyed Javad; Karbalaei, Sara Soleimani (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Elaborating on parallel, substitutional and correlated elements of the narrative in Yan Martel’s Life of Pi, this study aims at examining Martel’s technique for presenting a believable story in his novel. To discuss the way the believability of Pi’s narrative gets solidified, this enquiry takes advantage of the organizing principles of structuralism, namely, the metonymical-syntagmatic and the metaphorical-paradigmatic axes. Attributing the various correlating elements of the novel to these axes shows that what actually makes Pi a reliable narrator and simultaneously his narrative believable are the very parallel structures of the novel.